A case report of targeted therapy with apatinib in a patient with advanced gastric cancer and high serum level of alpha-fetoprotein. Issue 37 (September 2016) - Zhu, Xue-Ru; Zhu, Mei-Ling; Wang, Qing; Xue, Wen-Ji; Wang, Yi-Wei; Wang, Rui-Fen; Chen, Si-Yu; Zheng, Lei-Zhen
Abstract: Background: Alpha-fetoprotein (AFP) is an important marker for hepatocellular carcinoma, and the detection of serum AFP is currently the principle method for the diagnosis of hepatocellular carcinoma. The prevalence of gastric cancer (GC) with high level of serum AFP is extremely rare, but has unique clinical features. Case summary: We herein present a rare case with GC and high level of serum AFP. A 64-year-old Chinese female underwent gastrectomy was diagnosed as gastric adenocarcinoma and the pathological stage was T1b N0 M0, IA. With the progression of disease, the tumor widely metastasized and the serum AFP level increased progressively with the highest level of 3396 ng/mL. She successively entered into 3 lines palliative systematic chemotherapy and fourth-line targeted therapy of apatinib, a small molecule tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor-2. Although previous studies suggested that the prognosis of this special type of GC was poor, this patient lived for 22 months after tumor transfer. Apatinib kept her progression-free survival for 5 months, and the overall survival was 4.5 years. Conclusion: So, we speculate that maybe we can focus apatinib on serum AFP elevated GC patients.